Damage detection of bridge structures under changing environmental and operational conditions - Soo Lon Wah, William Soo Pow Kune (2019)
This thesis is focused on developing a vibration-based damage detection method to analyse bridge structures subjected to changing environmental and operational conditions by establishing an effective baseline to represent the undamaged state of the structures. The thesis is divided into two parts.